2016
DOI: 10.1021/acs.jafc.6b02534
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Application of Oligochitosan and Chitosan Reduces Calyx Alterations of Citrus Fruit Induced by Ethephon Degreening Treatment

Abstract: In the present study, we investigated whether the postharvest application of oligochitosan and chitosan could be used as potential alternatives to 2,4-dichlorophenoxyacetic acid (2,4-D) treatment to prevent calyx senescence of mandarin fruits induced by degreening treatment. The results of scanning electron microscopy indicated that the ethephon degreening treatment could accelerate the formation of pedicel abscission layers. Treatments with 15 g kg oligochitosan, 5 g kg chitosan, and 50 mg kg 2,4-D significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The activity of cell wall-degrading enzymes is an important factor affecting the postharvest abscission of fruit. The activity of various cell wall-degrading enzymes, including PG, POD, Cx, LOX and PE, changed signi cantly during grape fruit abscission (Chen et al, 2019), a pattern that has also been observed in other horticultural products, such as longkong, citrus and tomato fruit (Tsuchiya, et al, 2015;Deng, et al, 2016, Taesakul et al, 2018. The activity of cell wall-degrading enzymes is affected by various factors, such as application of 1.5 mM salicylic acid before harvest can inhibit their activity and prevent the softening of grapes .…”
Section: Discussionmentioning
confidence: 94%
“…The activity of cell wall-degrading enzymes is an important factor affecting the postharvest abscission of fruit. The activity of various cell wall-degrading enzymes, including PG, POD, Cx, LOX and PE, changed signi cantly during grape fruit abscission (Chen et al, 2019), a pattern that has also been observed in other horticultural products, such as longkong, citrus and tomato fruit (Tsuchiya, et al, 2015;Deng, et al, 2016, Taesakul et al, 2018. The activity of cell wall-degrading enzymes is affected by various factors, such as application of 1.5 mM salicylic acid before harvest can inhibit their activity and prevent the softening of grapes .…”
Section: Discussionmentioning
confidence: 94%
“…During degreening treatment, ethylene application has been reported to increase the activity of both polygalacturonic acid enzyme (PG) and cellulase (Cx), which promote browning and calyx abscission [33]. The incidence of calyx senescence triggered by degreening depends mainly on the ethylene concentration and process duration [26,30,34], and it is also very cultivar dependent.…”
Section: Calyx Senescencementioning
confidence: 99%
“…This auxin's mechanism of action is to reduce PG and Cx activities and to increase the lignin and water contents of fruit peel [37]. Despite this auxin having been widely employed and proving useful, it has been restricted by current European Union legislation, hence the need to find other synthetic auxins to avoid physiological changes in the calyx [33,35].…”
Section: Calyx Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Some natural food additives are reported to be used for preserving fruit and vegetables. For example, chitosan oligosaccharides can alleviate the calyx senescence of mandarin fruits by decreasing the abscisic acid content ( 19 , 20 ). Folic acid can inhibit the senescence of broccoli by improving the antioxidant capacity ( 21 ).…”
Section: Introductionmentioning
confidence: 99%